2013
DOI: 10.2166/aqua.2013.063
|View full text |Cite
|
Sign up to set email alerts
|

Better water quality and higher energy efficiency by using model predictive flow control at water supply systems

Abstract: Fifty-seven per cent of all water supply systems in the Netherlands are controlled by model predictive flow control; the other 43% are controlled by conventional level-based flow control. The differences between conventional level-based flow control and model predictive control were investigated in experiments at five full-scale water supply systems in the first half of 2011. Quality parameters of the drinking water and energy consumption of the treatment and distribution processes were measured and analysed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…The DWF prediction is obtained by a measurement data driven technique (Bakker et al, 2013a). Based on real-time measured water levels in the sewerage and both rainfall and DWF predictions, a discharge limitation is determined by a volume optimisation technique (Bakker et al, 2013b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DWF prediction is obtained by a measurement data driven technique (Bakker et al, 2013a). Based on real-time measured water levels in the sewerage and both rainfall and DWF predictions, a discharge limitation is determined by a volume optimisation technique (Bakker et al, 2013b).…”
Section: Methodsmentioning
confidence: 99%
“…This particular technique is based on the fully adaptive forecasting model for short-term drinking water demand (Bakker et al, 2013a). It is so generic that it can be applied to waste water discharge with some small adjustments of the settings.…”
Section: Dry-weather Flow Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows that model based control led to a 83% lower value for the production variation calculated with equation (1). Bakker et al (2013a) showed that treatment performance was better at lower values of production variation, resulting in lower values of the turbidity of the clear water. Pressure control Figure 6 and Figure 7 show trends of the water demand, the outlet pressure at the pumping station and the average pressure in the area of both examined periods.…”
Section: Figure 6: Difference Between Level Based (Upper Graph) and Mmentioning
confidence: 99%
“…Forecasting models are used by utilities around the world: In the Netherlands in 2012, 57% of all supplied water was controlled with predictive control models (Bakker et al, 2013a), leading to 5.2% lower energy costs and 19% lower turbidity of the clear water. Other examples of the implementation of predictive control are at four large utilities in the United States (Bunn and Reynolds, 2009), where a reduction of energy costs of 12% was achieved.…”
Section: Introductionmentioning
confidence: 99%